Morphology Matters: A Critical Reappraisal of the Clinical Relevance of Morphologic Criteria From the 2019 WHO Classification in a Large Colorectal Cancer Cohort Comprising 1004 Cases. (July 2021) - Jesinghaus, Moritz; Schmitt, Maxime; Lang, Corinna; Reiser, Marianne; Scheiter, Alexander; Konukiewitz, Björn; Steiger, Katja; Silva, Miguel; Tschurtschenthaler, Markus; Lange, Sebastian; Foersch, Sebastian; Becker, Karl F.; et al.
Abstract : The 2019 World Health Organization (WHO) classification of colorectal carcinoma (CRC) profoundly reclassified CRC subtypes and introduces tumor budding as a second major grading criterion, while condensing conventional grade into a 2-tiered system. So far it remains largely unexplored how these parameters interact with each other and whether they truly have an independent impact on patient prognosis. We reclassified a large single-center cohort of 1004 CRCs spanning 2 decades for adjusted WHO grade (low vs. high), tumor budding (Bd1/Bd2/Bd3), and CRC subtype (adenocarcinoma not otherwise specified, micropapillary, mucinous, serrated, medullary, adenoma-like, signet-ring cell, mixed adenoneuroendocrine carcinoma/neuroendocrine carcinoma, undifferentiated) according to the criteria of the 2019 WHO classification. We investigated the interaction of these parameters, their connection to stage/microsatellite status, and their significance for patient survival in the different subgroups. Specific subtypes other than adenocarcinoma not otherwise specified represented one third of all CRCs and were unevenly distributed throughout stage and microsatellite subgroups. Subtypes, WHO grade and tumor budding profoundly impacted all survival parameters ( P <0.001 for all analyses), with CRC subtypes and tumor budding—but not WHO grade—being stage-independent prognosticators for all survival comparisons. WHO grade had very limited prognostic value in CRC subtypes, while tumor budding retained its strong prognostic impact in most scenarios. Accurate delineation of CRC subtypes introduced in the 2019 WHO classification provides strong stage-independent prognostic information, arguing that they should be considered in pathology reports and in clinical trials. Of the morphology-based grading schemes included in the 2019 WHO, tumor budding outperforms WHO grade. Abstract : Supplemental Digital Content is available in the text.